AGB outflows as tests of chemical kinetics and radiative transfer models. Issue Volume 15:Issue S350(2019) (April 2019) - Van de Sande, M.; Danilovich, T.; Decin, L.
Abstract: The outflows of asymptotic giant branch (AGB) stars are important astrochemical laboratories, rich in molecular material and host to various chemical processes, including dust formation. Since the different chemistries are relatively easily probed, AGB outflows are ideal testbeds within the wider astrochemical community. Recent observations are pushing the limits of both our current chemical models and radiative transfer routines. Current chemical models are restricted by the completeness of their chemical networks and the accuracy of the reaction rates. The molecular abundances retrieved by radiative transfer routines are strongly dependent on collisional rates, which are often not measured or calculated for molecules of interest. To further our understanding of the chemistry within the outflow, collaboration with the laboratory astrophysics community is essential. This collaboration is mutually beneficial, as it in turn provides new science questions for laboratory experiments and computations.